THE INFLUENCE OF LIFESTYLE AND BRAND IMAGE ON COFFEE PURCHASE BEHAVIOUR AT COFFEE-TO-GO SHOP - Siti Nadira Nurdiyanti; Johan, Irni Rahmayani (Journal of Child, Family, and Consumer Studies, 2024)
The COVID-19 pandemic causes some changes on consumer behavior in buying products, including buying coffee at coffee-to-go shops. Moreover, lifestyle changes also occur in purchasing coffee. This study aims to analyze the influence of lifestyle and brand image on coffee buying behavior in coffee-to-go shops. The method used in this research was cross sectional design. The population in this study was Generation Z in the DKI Jakarta area, and the number of respondents were 146 respondents. Respondents were obtained by voluntary sampling technique. Data were collected through an online questionnaire using a Google form. The data obtained were analyzed using SPSS 25.0. The results show that there is a positive relationship between income per month, brand image and lifestyle. Moreover, income per month, lifestyle and brand image has a positive and significant relationship with coffee purchasing behavior. The results of multiple linear regression test indicate that lifestyle and brand image has a positive and significant effect on coffee purchasing behavior at coffee-to-go shops.